Dietary nitrate improves vascular function in patients with hypercholesterolemia: a randomized, double-blind, placebo-controlled study. Issue 1 (25th November 2015) - Velmurugan, Shanti; Gan, Jasmine Ming; Rathod, Krishnaraj S; Khambata, Rayomand S; Ghosh, Suborno M; Hartley, Amy; Van Eijl, Sven; Sagi-Kiss, Virag; Chowdhury, Tahseen A; Curtis, Mike; Kuhnle, Gunter GC; Wade, William G; et al.
ABSTRACT: Background: The beneficial cardiovascular effects of vegetables may be underpinned by their high inorganic nitrate content. Objective: We sought to examine the effects of a 6-wk once-daily intake of dietary nitrate (nitrate-rich beetroot juice) compared with placebo intake (nitrate-depleted beetroot juice) on vascular and platelet function in untreated hypercholesterolemics. Design: A total of 69 subjects were recruited in this randomized, double-blind, placebo-controlled parallel study. The primary endpoint was the change in vascular function determined with the use of ultrasound flow-mediated dilatation (FMD). Results: Baseline characteristics were similar between the groups, with primary outcome data available for 67 patients. Dietary nitrate resulted in an absolute increase in the FMD response of 1.1% (an ∼24% improvement from baseline) with a worsening of 0.3% in the placebo group ( P < 0.001). A small improvement in the aortic pulse wave velocity (i.e., a decrease of 0.22 m/s; 95% CI: −0.4, −0.3 m/s) was evident in the nitrate group, showing a trend ( P = 0.06) to improvement in comparison with the placebo group. Dietary nitrate also caused a small but significant reduction (7.6%) in platelet-monocyte aggregates compared with an increase of 10.1% in the placebo group ( P = 0.004), with statistically significant reductions in stimulated (ex vivo) P-selectin expression compared with the placebo group ( P < 0.05) but no significant changes in unstimulated expression. No adverse effects of dietary nitrate were detected. The composition of the salivary microbiome was altered after the nitrate treatment but not after the placebo treatment ( P < 0.01). The proportions of 78 bacterial taxa were different after the nitrate treatment; of those taxa present, 2 taxa were responsible for >1% of this change, with the proportions of Rothia mucilaginosa trending to increase and Neisseria flavescens ( P < 0.01) increased after nitrate treatment relative to after placebo treatment. Conclusions: Sustained dietary nitrate ingestion improves vascular function in hypercholesterolemic patients. These changes are associated with alterations in the oral microbiome and, in particular, nitrate-reducing genera. Our findings provide additional support for the assessment of the potential of dietary nitrate as a preventative strategy against atherogenesis in larger cohorts. This trial was registered at clinicaltrials.gov as NCT01493752.